The potency of Elaeocarpus grandiflorus Leaf Extract as Anti-obesity: in vivo and in silico Study - Nugrahaningsih, WH; Ramasamy, Sujatha; Laraswati, Vivi Anggraeni; Yuniastuti, Ari; Christijanti, Wulan (Universitas Negeri Semarang, 2024)
The research aims to determine the effect of ethanol extract of Elaeocarpus grandiflorus leaves extract as anti-obesity by in vivo and silico computational models. The pre-and -post-tests were carried out on 20 female Wistar rats, divided into 4 groups. The control group (K) received no treatment and the experimental groups were treated with E. grandiflorus extract of 200 mg/kg BW (P1), 400 mg/kg BW (P2), and 800 mg/kg BW (P3) for 14 days. The body weight, abdominal circumference, and abdominal fat mass were measured on Day 1 and Day 15. The results showed differences in body weight (p=0.02), abdominal circumference (p=0.01), and abdominal fat mass (p=0.00). In silico exploration, bioactive compounds of rutin, orientin, luteolin, vitexin, iso orientin, isovitexin, kaempferol, and quercetin were identified, and targeted ELAVL1, IGF1R, CREB1, AKT1, and PIK3R1 of the AMPK signaling pathway that involved in the anti-obesity mechanism. The high binding affinity values was rutin-EVAL1 (-9.3), orientin-ELAVL1 (-8.3), and quercetin- IGFR1 (-8.2). It can be concluded that the ethanol extract of E. grandiflorus leaves has the potential to be developed as an anti-obesity agent.